2016
DOI: 10.1111/jcal.12161
|View full text |Cite
|
Sign up to set email alerts
|

The use of gamification in education: a bibliometric and text mining analysis

Abstract: The use of games in education represents a promising tool to motivate and engage students in their learning process. Most of previous research on the topic has focused to develop theoretical frameworks or to conduct experiments as a means to analyse learning outcomes such as knowledge retention, problem-solving skills gains or attitudes toward game-based learning. Nevertheless, little research has focused on providing a comprehensive literature review, which will help researchers to better understand how this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
0
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(119 citation statements)
references
References 31 publications
4
87
0
10
Order By: Relevance
“…This article presents a number of results about game-based learning in order to highlight more adequate and effective trends and practices. As this is a recently developed subject, there is still the possibility to expand already available knowledge through literature reviews (Hamari et al, OPEN ACCESS 2014;Martí-Parreño, Méndez-Ibáñez, & Alonso-Arroyo, 2016;Nah, Zeng, Telaprolu, Ayyappa, & Eschenbrenner, 2014;Surendeleg, Murwa, Yun, & Kim, 2014). The main goal of this article is to develop a conceptual research model of applying games to management education based on a systematic literature review that focuses on the most relevant literature regarding the application of gamification to educational contexts in order to grasp gamification's main themes and constructs.…”
Section: Introductionmentioning
confidence: 99%
“…This article presents a number of results about game-based learning in order to highlight more adequate and effective trends and practices. As this is a recently developed subject, there is still the possibility to expand already available knowledge through literature reviews (Hamari et al, OPEN ACCESS 2014;Martí-Parreño, Méndez-Ibáñez, & Alonso-Arroyo, 2016;Nah, Zeng, Telaprolu, Ayyappa, & Eschenbrenner, 2014;Surendeleg, Murwa, Yun, & Kim, 2014). The main goal of this article is to develop a conceptual research model of applying games to management education based on a systematic literature review that focuses on the most relevant literature regarding the application of gamification to educational contexts in order to grasp gamification's main themes and constructs.…”
Section: Introductionmentioning
confidence: 99%
“…On another of our previous works, we demonstrated that the improvement in knowledge is also statistically significant when the students play in pairs and also in large groups (up to 12 children) (Martín-SanJosé et al 2015). These results are in line with previous works that have argued for the immense potential of educational computer games in helping students to improve their learning performance (e.g., Hwang and Wu 2012;Martí-Parreño, Méndez-Ibáñez, and Alonso-Arroyo 2016).…”
Section: Vr System For Dental Learningsupporting
confidence: 91%
“…Of these 34, only two studies looked at gamification in online classes. A later study, with less stringent selection criteria, identified 139 articles on gamification in educational settings between 2010 and 2014, but went into little detail about the overall content of those articles or what levels of education they addressed [21].…”
Section: Introductionmentioning
confidence: 99%